ASESMEN RISIKO BENCANA GEMPA TERHADAP PERUMAHAN WARGA DI KOTA PADANG - Rafki Imani; Rita Nasmirayanti; Farhan Febrizoni; Deded Eka Sahputra (JURNAL RIVET, 2026)
The building of Boarding houses are one form of urban housing with relatively high vulnerability to disasters, especially in densely populated and earthquake-prone areas such as Padang City. This study aims to evaluate the level of disaster risk in boarding house buildings through the integration of structural, non-structural, and non-technical assessments. The research was conducted using a descriptive quantitative approach based on a case study of a two-story boarding house in Lubuk Begalung District, Padang City. Data were collected through field observations, visual documentation, and interviews with the building owner. Risk assessment was carried out using a semi-quantitative method with hazard, vulnerability, and impact parameters on a scale of 1–5. The analysis results show that the main structure of the building is in fairly good condition, but hairline cracks were found on the walls, evacuation routes are narrow, and there is no availability of fire extinguishers, evacuation signs, or emergency response SOPs. The risk value for earthquake hazards is 73.4 (very high category), while for fire hazards it is 58.7 (high category). These findings indicate that the high level of risk is more influenced by weaknesses in non-structural and non-technical aspects compared to the condition of the main structure. This study emphasizes the importance of a mitigation approach that integrates physical improvements to the building with the enhancement of residents’ capacity and preparedness.